Beyond individual choice: Exploring pathways linking couple dynamics with Unintended Pregnancy and Birth in India - Monika Lakhotia; Bhaswati Das (PLoS ONE, 2026)
Couple power dynamics are known to influence sexual agency and reproductive health, yet this negotiation process within marital relationships remains empirically underexamined in India’s public health discourse. This study investigates Unintended Pregnancy and Birth (UPB) as an outcome associated with relational systems involving husbands’ sexual attitudes (normative context), wives’ health autonomy (negotiated agency), and Intimate Partner Violence (IPV; structural constraint). Using a sample of 19,896 couples from NFHS-5 (2019−21), we conducted bivariate and multivariate logistic regressions to identify patterns of UPB. Subsequently, a Generalized Structural Equation Model (GSEM) was used to test the mediating role of wives’ health autonomy on the pathway between husbands’ attitudes and UPB. To explore the moderating role of IPV between wives’ health autonomy and UPB, we used an interaction term. Findings show that overall, 8.30% of pregnancies and births are unintended. While wives’ health autonomy significantly reduces the risk of UPB, IPV act as the persistent structural constraint that elevates UPB. Furthermore, husbands’ regressive sexual attitudes, reflecting a normative climate of sexual entitlement, indirectly increased the likelihood of UPB by significantly restricting wives’ health autonomy. These findings highlight how intimate power asymmetries and normative constraints shape reproductive experiences. Addressing UPB, which reflects compromised autonomy and gender control, requires gender-transformative approaches that go beyond individual interventions to challenge inequitable norms, engage both partners and strengthen agency within intimate relationships to support reproductive well-being.